Please don't eat me - Climo, Liz (New York ; Little, Brown and Company, 2019)
A rabbit tries everything he can think of to prevent a hungry bear from eating him, but the bear has something else in mind.
107825
Keywords: Friendship -- Juvenile fiction; Animals; Rabbits; Bears; Humorous stories; Animals / Rabbits; Children's stories; Humorous stories; Picture books; Fiction; Juvenile works